HEALTH CONSEQUENCES OF NUTRITION IN CILHOOD AND EARLY INFANCY: A SYSTEMATIC REVIEW - M. Hadi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Nutrition affects health even in the womb. Early diet impacts metabolism and body composition. Feeding habits—the cornerstone of nutrition—are influenced by personal and familial behaviors, maternal education, social status, and culture. Breast milk, formula, and supplements nourish babies and toddlers. Aim: The goal of this study is to showed health consequences nutrition childhood early infancy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 48 articles, whereas the results of our search on SagePub brought up 22 articles. The results of the search conducted for the last year of 2013 yielded a total 18 articles for PubMed and 7 articles for SagePub. In the end, we compiled a total of 12 papers, 8 of which came from PubMed and 4 of which came from SagePub. We included six research that met the criteria. Conclusion: Length affects LAS, MUAC and WLZ body composition relationships differently. Study consist showed WLZ is a good tissue mass marker regardless of length. The MUAC combines tissue mass and length to measure inadequate growth.